Degree of Functionality and Perception of Health-Related Quality of Life in People with Moderate Stroke: Differences between Ischemic and Hemorrhagic Typology - Iratxe Unibaso-Markaida; Ioseba Iraurgi; Nuria Ortiz-Marqués; Silvia Martínez-Rodríguez (Behavioural Neurology)
Objectives. The objectives of this pilot study were to analyze the functional differences and the differences regarding the perception of health-related quality of life between people affected by ischemic and hemorrhagic stroke, respectively, and between these and their normative groups. Methods. A pre-post design study was conducted with 30 patients aged 65±15 during eight weeks. It assessed disability, mobility, and health-related quality of life. Exact nonparametric tests were used to compare both types of stroke, and t-tests and effect size estimates were employed to compare the stroke group and the normative group. Results. At baseline, there were differences in disability (“getting along” domain), where a poorer result was obtained by the hemorrhagic stroke group, and in the “vitality” and “mental health” domains of the health-related quality of life test, where the ischemic group obtained poorer results. Both groups made significant progress in their health assessments and functionality after eight weeks, and no significant differences were found between them at that time. The scores obtained in both groups differed statistically from the normative values, both at baseline and at posttest. Conclusions. Regardless of the stroke type, divergent results were only found in two domains, “vitality” and “mental health.” There was an improvement over time, but the scores obtained were still lower than those observed in the normative group, which indicated that the participants’ health was highly compromised. This study provides more information for faster rehabilitation after stroke; even so, more studies are needed.